Application of Laser Cladding Additive Manufacturing Technology in TRT Blade Manufacturing and Repair Process (Journal of Global Humanities and Social Sciences, 2024)
TRT blades, as the core components of turbojet engines, carry huge high temperature and high pressure working environment and complex mechanical stresses, and their manufacturing and repair processes have extremely strict requirements on materials and processes. Traditional repair methods are often faced with the problems of material waste, difficulty in recovering complex geometric structures, and difficulty in guaranteeing repair results. Laser cladding additive manufacturing technology, with its precise material deposition and efficient repair process, brings new opportunities for the manufacturing and repair of TRT blades. The purpose of this paper is to explore the key technology of laser cladding technology in improving the blade performance and optimizing the repair process and its practical effect in dealing with the complex working environment through the in-depth study of the application of laser cladding technology in TRT blades.